Avoidance and personal and occupational quality of life in French people with driving anxiety. (July 2021) - Fort, A.; Collette, B.; Evennou, M.; Jallais, C.; Charbotel, B.; Stephens, A.N.; Hidalgo-Muñoz, A.
Highlights: This is the first survey among a French population experiencing driving anxiety. Respondents are classified as mildly (32%), moderately (45%) or extremely (23%) anxious. The three groups report different impacts on daily and occupational life. The extremely anxious group report stronger effects on quality of life and work. The distinction of these three intensity levels is important in further research. Abstract: Driving anxiety can have a significant impact on one's quality of life, particularly for those who experience intense levels. However, to date there are limited data about the perceived impact of driving anxiety on occupational life, and driving anxiety remains under-researched in France. To address this gap, an online survey assessing self-reported driving anxiety, how it manifests and its links with some aspects of personal and occupational life was designed. The survey was administered in France to respondents who identified as experiencing driving anxiety. Responses were obtained from 304 people aged 18 years or older. In the sample, 32.2%, 44.7% and 23% respectively reported mild, moderate and extreme levels of driving anxiety. In the extremely anxious group, males were under-represented, whereas people aged 35–44 and unlicensed drivers were over-represented. People who were unemployed (excluding students and retired people), reported that their anxiety had been a barrier to getting a job and a high percentage of these respondents had also previously considered leaving a position because of their anxiety. Respondents also reported their anxiety had a negative impact on their perceived quality of life in general. People who categorised as extremely anxious reported a negative impact four times higher than those in the mildly anxious group. The results highlight for the first time the perceived impact of driving anxiety on daily and occupational life in a French population. Further, the results demonstrate the importance of distinguishing between moderately and extremely anxious drivers as the intensity level has differential impacts on personal and work life quality.